Health psychology theory, research and practice - Marks, David (David F.); Murray, M. 1952-; Estacio, Emee Vida (Los Angeles SAGE, 2018)
"The fifth edition of this essential text further advances a critical perspective on health while introducing readers to emerging issues such as long-term conditions and end-of-life care."--Cover, p.[4]
Part 1: Health psychology in the context of biology, society and methodology. -- 1. Health psychology: an introduction -- 2. The nervous, endocrine and immune systems and the principle of homeostasis -- 3. Genetics, epigenetics and early life development -- 4. Macro-social influences -- 5. Social justice -- 6. Culture and health -- 7. An A-Z of research methods and issues relevant to health psychology -- Part 2: Theories, models and interventions for health behavior change. -- 8. Theories, models and interventions -- 9. Sexual health -- 10. Food, eating and obesity -- 11. Alcohol and drinking -- 12. Tobacco and smoking -- 13. Physical activity and exercise -- Part 3: Health promotion and disease prevention. -- 14. Information, communication and health literacy -- 15. Lay representations of health and illness -- 16. Screening and immunization -- 17. Health promotion -- Part 4: Illness experience and health care. -- 18. Illness and personality -- 19. Medicine taking: adherence and resistance -- 20. Pain and pain control -- 21. Cancer -- 22. Coronary heart disease -- 23. HIV infection and AIDS: the pinnacle of stigma and victim blaming -- 24. Long-term conditions: diabetes and ME/CFS -- 25. End-of-life care, dying and death.
Previous edition entered under title.
Prof. Generelao (Recommending faculty) - Bookfair 2019
Includes bibliographical references (pages 665-779) and index.
Keywords: Clinical health psychology; Health Behavior; Preventive Medicine; Risk Factors